Participation of an NGO in international scientific cooperations - Andrea, Ferenczi (Magyar Gerontológia, 2023)
The AWCDH has set itself the goal of recognizing, understanding, fostering and honoring the need for women’s career development in the family and beyond. We help women find career opportunities by providing information, advice and training so that with their newfound knowledge, talent, and female values specific to them, they can make meaningful contributions to the business, academic and non-profit spheres.